Platsens sanning. Performativitet och gränsdragningar i tornedalsk litteraturhistoria och grammatik - Heith, Anne (Nordlit, 2012)
The language Meänkieli is an official minority language in Sweden since the year 2000. The acknowledgement of the existence of historical linguistic minorities reflects the fact that Sweden has always been a multiethnic and multilingual space. Long before the present day borders were established there were Sami people and Finno-Ugric groups of people in the northernmost parts of Scandinavia. Since a couple of decades the cultural mobilization among the Swedish Tornedalians has been intensified. Publishing houses which publish in Meänkieli (previously called Tornedalian Finnish) have been established. Furthermore there are conscious attempts at constructing a literary tradition and at producing grammar books of Meänkieli. In 2007 the first volume of a Tornedalian literary history co-authored by Bengt Pohjanen and Kirsti Johansson was published, Den tornedalsfinska litteraturen. Från Kexi till Liksom. Two years later a second volume, Den tornedalsfinska litteraturen. Från Kalkkimaa till Hilja Byström, was published. Both volumes performatively construct a specific Tornedalian literary tradition which is distinguished from a Swedish national tradition. This may be interpreted as a deconstruction of notions of a homogeneous Swedish nation through the production of local truths which challenge culturally homogenizing nation-building.